IMPACTO DA VIOLÊNCIA OBSTÉTRICA NA SAÚDE FÍSICA E EMOCIONAL DAS MULHER BRASILEIRAS - Halyson de Oliveira Gomes, Tiago; Nascimento, Maria Eduarda Bezerra do; Eduardo Amorim Mesquita, Fillipe; Francisca Araújo de Freitas Cavalcante , Maryane; Macedo Aguiar , Brenda; Fellipe Alves de Souza , Alysson; Souza de Alcântara , Maria Noêmia; Gomes Campos , Adilson; Aparecida Mendes Ribeiro , Mayra; Evellyn da Silva , Beatriz; Pinheiro da Silva , Laís; Oliveira de Melo, Ana Beatriz (Brazilian Journal of Implantology and Health Sciences, 2024)
This study addresses the role of the obstetric nurse in the context of humanized natural childbirth, highlighting the relevance of humanization in childbirth care and the challenges faced in teaching hospital institutions. The research discusses evidence-based practices, such as respect for women's autonomy, encouraging the mother-baby bond, and reducing unnecessary interventions, in addition to emphasizing the fight against obstetric violence. The results reinforce the importance of the nurse's role as a mediator in woman-centered care, promoting safety, support, and well-being during the childbirth process.